التفرد وأثره في تعليل الأحاديث من خلال كتاب "علل الحديث لابن أبي حاتم" (نماذج تطبيقية من أبواب الطهارة) - معمري, عیسى (University of eloued جامعة الوادي, 2016)
هذه الرسالة بعنوان: (التفرد وأثره في تعلیل الأحادیث من خلال كتاب "علل الحدیث لابن أبي حاتم")، اشتملت على د ا رسة التفرد في روایة الأحادیث، وتهدف هذه الد ا رسة إلى تبیین أثر التفرد في التعلیل، معتمدا على منهج النقاد في ذلك قدر المستطاع، وقد تطرقت لد ا رسة التفرد، من جانبین: أولا:_ جانب نظري: وفیه بینت تعریف التفرد لغة واصطلاحا وأقسامه وأسباب وقوعه، ومظانه والق ا رئن التي تساعد على قبول التفرد أو رده، وعلاقته بعلوم الحدیث. ثانیا:_ جانب تطبیقي: خرجت فیه ثمانیة أحادیث منتقاة من كتاب (علل أخبار رویت في الطهارة)، وفیه أیضا عرفت بابن أبي حاتم وأبیه وأبي زرعة، وعرفت بكتاب العلل له، ثم ختمت الفصل التطبیقي، بملحق سردت فیه ما لم أخرجه من الكتاب مما فیه تفردات مع شرح موجز لتعلیل الحدیث في الكتاب، والأمثلة الثمانیة المنتقاة كلها بأسانید جیادThe title of this dissertation is:( " uniqueness and its effect on hadith's problems "- depending on ILAL ALHADITH of abu hatem ) it embodied the this study aims to explain the ، study of uniqueness using the ،effect of uniqueness on extracting the problems of hadith method of the critics as much as possible. I have studied the uniqueness from two aspects : first :theoretical part : in this part i mention the definition of uniqueness lexically and contextually and its forms also the reasons ، its reference and either approval or refusal proofs ،of its occurrence and its relationship to Hadith studies . Second : practical part : in this part i authenticate eight (8) ahadith selected from the book ILAL AKBAR ROWYAT FI ALTHARA then i define IBN ABI HATEM and his father and ABI ZORAA also ، after that i conclude the practical part ،his book KITABOLILAL i list in it what i didn't authenticate from the ،with an extension، uniqueness in the book ILAL AKBAR ROWYAT FI ALTHARA with a and all ،brief explanation about hadith 's problems in the same book the previous eight (8) examples are based on a trusted references .
ماستر علوم الحديث
Keywords: التفرد,الأحاديث,كتاب; exclusivity, hadiths, book